Judging the judges` performance in rhythmic gymnastics - Flessas, K.; Mylonas, D.; Panagiotaropoulou, G.; Tsopani, D.; Korda, A.; Siettos, C.; Di Cagno, A.; Evdokimides, I.; Smyrnis, N. (Medicine & Science in Sports & Exercise, 2015)
Introduction: Rhythmic gymnastics (RG) is an aesthetic event balancing between art and sport that also has a performance rating system (Code of Points) given by the International Gymnastics Federation. It is one of the sports in which competition results greatly depend on the judges` evaluation. In the current study, we explored the judges` performance in a five-gymnast ensemble routine.